HUBUNGAN ANTARA KETERAMPILAN KOMUNIKASI DENGAN AKTIVITAS BELAJAR PESERTA DIDIK DI SMA N 2 SOLOK SELATAN - Nirmala, Dona Gusti (Bimbingan dan Konseling, 2014)
One of the activities carried learners in learning is communicating. In the learning processof students are less skilled in communicating and impact on learners learning activities. Based onthe above background, the formulated problems, relationship communication skills with learnerslearning activities in SMA N 2 Solok south. (1) describe the communication skills of high schoolstudents in South Solok N 2, (2) describe the activities of learners in South Solok SMA N 2, (3)the relationship of communication . This type of research is descriptive correlational study with apopulation of students of class X, XI and XII, amounting to 415 people and 81 samples. Samplingusing stratified random sampling technique.To analyze the data communication skills. whereashypothesis testing to see the relationship with the communication. The results of data analysis: (1)A description of communication skills profiles of high school students in South Solok N 2 is atwell with the percentage of 53.09%, (2) description of the activity profile of learners in SouthSolok SMA N 2 are in the category less well with the percentage of 54.32%, (3) Relationship withthe communication skills learning activity rhitung obtained for 0.401> of rtabel at 0,361 In 81 dfwith significance level of 0.000 (sig <0.05). So the results, the relationship betweencommunication skills with learners learning activities in SMA N 2 South Solok are at a significantlevel.